Analisis Faktor Penyebab dan Dampak Terjadinya Bullying Pada Siswa Kelas 6 SD Inpres Nitneo - Habibi Musa; Delti Taneo; Dalle, Juwitni Marleni Luisa (STKIP Andi Matappa Pangkep, 2024)
This study aims to determine the causal factors and impact of bullying on grade 6 students at Nitneo Elementary School. Using a quantitative approach through a questionnaire instrument, the study population consisted of 30 students, consisting of 12 boys and 18 girls. The results showed that the factors that cause bullying include family factors that are less harmonious, a school environment that has a negative climate, peer pressure, the influence of misused social media, physical deficiencies that make students targeted, and economic factors that create inequality. Forms of bullying that are often encountered are verbal, physical, social, and cyberbullying behaviors. The impact of bullying is detrimental, including stress, decreased learning achievement, behavioral changes, physical health problems, and feelings of sadness and disappointment. To deal with and prevent bullying, some steps that can be taken are providing education about bullying to students, training teachers in handling bullying cases, increasing supervision in school areas, and providing reporting channels for students. This study concludes that bullying has a great influence and can permanently imprint on the survival of students who experience it.